El reciclaje como estrategia para potenciar la educación ambiental en el área de ciencias naturales de los niños y niñas del cuarto grado del subnivel básica media de la escuela de educación general básica Adolfo Jurado González, parroquia el sagrario, cantón y provincia de Loja, periodo académico 2014 – 2015 - Gaona Ruiz, Maria Fernanda (2016)
The research called recycling as a strategy to enhance environmental education in the area of natural sciences children fourth grade Sublevel Basic Media School of General Education Basic Adolfo Jurado Gonzalez, parish tabernacle Region and province of Loja , academic period 2014 - 2015, had the overall objective to implement recycling as a strategy to enhance environmental education in the area of Natural Sciences of the children in the fourth grade of elementary and middle sublevel school General education Basic Adolfo Jurado Gonzalez , parish El Sagrario Region and province of Loja, academic 2014-2015. The research design was pre-experimental and transversal, scientific, inductive, deductive, analytical, synthetic and descriptive methods that allowed collect, interpret and analyze the information was used; the technique used was the survey conducted by questionnaire instrument to thirty-one students; and the same applied to model questions to the teacher; since it was concluded that the contribution of the strategy of recycling through workshops on the development of environmental education is significant, since it allowed enhance the practice of it in students, so it is recommended that workshops of recycling part of the teaching and authorities to implement the strategies in the area of Natural Sciences, to encourage students, the application knowledge acquired through reflective processes of reality, in solving environmental problems.